Asupan energi dan konsumsi makanan ringan berhubungan dengan kejadian gizi lebih pada remaja di SMA Islam AL-AZHAR 1 Jakarta - Waode Nurhafiza Indah Mukhlisa; Leni Sri Rahayu; Mohammad Furqan (ARGIPA (Arsip Gizi dan Pangan), 2018)
Overweight can be one of some reasons that cause non-infectious diseases. It is caused by there is no balancing between their energy intake, snack and flavored drink consumption. This study aims to determine the relation of energy intake, consuming some snacks and sweet drinks with the case of overweight in adolescents was aged between 16-18 years old at SMA Islam Al-Azhar 1 Jakarta. This research used cross-sectional design with proportionate stratified random sampling. Number of subjects in this study was 120 adolescents, mostly boys. The result of this study showed most of subjects were having nutritional excess status overweight (50,8%), excessive energy intake (60%), excessive snack consumption(52,5%), and appropriate flavored drink consumption (55,8%). Chi-square test showed there was a relation between energy intake (p<0,05) and snack consumption (p<0,05) with overweight. There was no relation between flavored drink consumption with overweight (p>0,05).